2014
DOI: 10.3390/e16063049
|View full text |Cite
|
Sign up to set email alerts
|

Using Permutation Entropy to Measure the Changes in EEG Signals During Absence Seizures

Abstract: Abstract:In this paper, we propose to use permutation entropy to explore whether the changes in electroencephalogram (EEG) data can effectively distinguish different phases in human absence epilepsy, i.e., the seizure-free, the pre-seizure and seizure phases. Permutation entropy is applied to analyze the EEG data from these three phases, each containing 100 19-channel EEG epochs of 2 s duration. The experimental results show the mean value of PE gradually decreases from the seizure-free to the seizure phase an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 56 publications
0
75
0
Order By: Relevance
“…Comparison with the conventional entropy methods with a classification accuracy of 86.1%, the classification rate was 90% with a MPE index 2 . Similarly, Li Jing et al using permutation entropy, an examination was implemented to determine whether EEG data changes can detect various states of human absence epilepsy 1 . The average PE values have been shown to gradually decrease from no seizure to seizure state and provide evidence that three different phases of seizure in absence epilepsy can be detectable.…”
Section: Axis Of Least Inertiamentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison with the conventional entropy methods with a classification accuracy of 86.1%, the classification rate was 90% with a MPE index 2 . Similarly, Li Jing et al using permutation entropy, an examination was implemented to determine whether EEG data changes can detect various states of human absence epilepsy 1 . The average PE values have been shown to gradually decrease from no seizure to seizure state and provide evidence that three different phases of seizure in absence epilepsy can be detectable.…”
Section: Axis Of Least Inertiamentioning
confidence: 99%
“…About 80% of people with epilepsy live in developing countries. 1 Today, people with epilepsy and their families suffer from social discrimination and social stigma in many parts of the world. Epileptic seizures can be associated with impairment or loss of consciousness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The EEG dataset was recorded from pediatric subjects with intractable seizures at Children's Hospital Boston. This database contains 22 subjects (17 females, ages 1.5-19; 5 males, ages [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] and can be downloaded from the PhysioNet website: http://www .physionet.org/pn6/chbmit/. The International 10-20 system of EEG electrode positions and nomenclature was used to collect these EEG recordings.…”
Section: Eeg Datasetsmentioning
confidence: 99%
“…Li et al used another order pattern based entropy method (called permutation entropy, PE) as an indicator to predict the epileptic seizures in genetic absence epilepsy rats, and the results showed that PE can successfully detect preseizure phase in 169 of 314 seizures (54%), which was higher than SE (21%) in [12]. Permutation entropy was also applied to analyzing EEG data in patients with epilepsy, which demonstrated that the EEG during the seizure-free phase is characterized by a higher value of permutation entropy than the EEG during the seizure phase [13,14].…”
Section: Introductionmentioning
confidence: 99%